ПЛАНУВАННЯ Й ОРГАНІЗАЦІЯ ДІЯЛЬНОСТІ МАРКЕТИНГОВИХ КАНАЛІВ ПІДПРИЄМСТВА - Харута В. С.; Головко Б. С. (World Science, 2019)
The article substantiates the need for domestic enterprises to plan and organize the activities of marketing distribution channels. The most important problems related to the aspects of distribution channels functioning, which hinder the development of marketing policy in Ukraine, are highlighted. The ways to solve these problems are suggested.